2014
DOI: 10.1016/j.aquatox.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low-level domoic acid exposure alters gene transcription and impairs mitochondrial function in the CNS

Abstract: Domoic acid is an algal-derived seafood toxin that functions as a glutamate agonist and exerts excitotoxicity via overstimulation of glutamate receptors (AMPA, NMDA) in the central nervous system (CNS). At high (symptomatic) doses, domoic acid is well-known to cause seizures, brain lesions and memory loss; however, a significant knowledge gap exists regarding the health impacts of repeated low-level (asymptomatic) exposure. Here, we investigated the impacts of low-level repetitive domoic acid exposure on gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 39 publications
0
34
1
Order By: Relevance
“…The effects of chronic low-level asymptomatic exposure have not been well studied and are of particular concern for coastal communities including recreational and Tribal harvesters who regularly consume shellfish such as razor clams that are known to retain low levels of DA in edible tissues for more than a year after HAB events (Lefebvre and Robertson, 2010; Wekell et al, 1994). In a study with long-term whole animal exposures to low asymptomatic doses of DA, zebrafish ( Danio rerio ) had altered gene transcriptomes and impaired mitochondrial function in whole brains after nine months of weekly exposures (Hiolski et al, 2014). Additionally, chronic low-level exposure did not confer resistance to DA, but instead increased toxin sensitivity making the neurologic effects of subsequent exposures more pronounced in chronically exposed animals (Hiolski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of chronic low-level asymptomatic exposure have not been well studied and are of particular concern for coastal communities including recreational and Tribal harvesters who regularly consume shellfish such as razor clams that are known to retain low levels of DA in edible tissues for more than a year after HAB events (Lefebvre and Robertson, 2010; Wekell et al, 1994). In a study with long-term whole animal exposures to low asymptomatic doses of DA, zebrafish ( Danio rerio ) had altered gene transcriptomes and impaired mitochondrial function in whole brains after nine months of weekly exposures (Hiolski et al, 2014). Additionally, chronic low-level exposure did not confer resistance to DA, but instead increased toxin sensitivity making the neurologic effects of subsequent exposures more pronounced in chronically exposed animals (Hiolski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have shown the potential for human health impacts from chronic, low level DA exposure. Repetitive, low dose experiments simulating chronic exposure have shown increased toxin susceptibility and impaired mitochondrial function in zebrafish after 20 weeks and 18 weeks respectively (Hiolski et al 2014; Lefebvre et al 2012). Truelove et al (1996) and Truelove et al (1997) found no signs of toxicity after repeated, low dose DA exposure in cynomolgus monkeys (30 day exposure) and rats (64 day exposure), although these studies focused on traditional clinical indicators of toxicity such as gross histologic lesions and blood chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic low level DA exposure (i.e. levels below those that cause the overt signs of toxicity listed above) has been connected to increased toxin susceptibility and impaired mitochondrial function in laboratory studies, and potential memory deficits in humans (Grattan et al 2016; Hiolski et al 2014; Lefebvre et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, exhaustive monitoring of Pseudo-nitzschia has not been carried out to date in Japanese coastal waters. More recent studies have indicated that chronic exposure to even low levels of DA in humans can cause negative effects at the cellular level, which may in turn cause chronic health problems (Hiolski et al 2014). Thus, monitoring programs that focus only on the detection of DA concentrations higher than the regulatory limit in shellfish do not guarantee the safety of food or the protection of human health.…”
Section: Checks Of Primer Universality and Specificitymentioning
confidence: 99%